Physical activity and cognitive impairment among the elderly in some districts of Ha Nam province in 2018 - Van, Hoang Thi Hai; Son, Dao Anh; Thai, Pham Quang (Tạp chí Y học Dự phòng, 2021)
The study was conducted on 1,210 elderly people (aged 60 and older) with the purpose of understanding physical activity and cognitive impairment among elderly people in some districts of Ha Nam province in 2018. The results showed that the percentage of elderly people with symptoms of cognitive impairment was high, accounting for 46.36%. There was a significant difference between the rate of cognitive impairment of the group who exercised frequently (41.92%) and that of the group who did not exercise (51.62%) (p<0.05). Compared to the Non-exercise group, the risks of cognitive impairment of group exercise 15 - 45 minutes/week (OR = 0.69; 95% CI: 0.51 - 0.93); group exercise 45 - 90 minute/week group (OR = 0.61; 95% CI: 0.44 - 0.84) and group exercise Over 90 minutes/week (OR = 0.43; 95% CI: 0.27 - 0.67) were all significantly lower. The more time the research subjects exercise, the lower their risk of developing cognitive impairment became. Our finding suggests that physical activities may delay or prevent the onset of cognitive impairment in elderly people. It is necessary to expand research, continue to apply the cognitive screening test based on international standards, while guiding and encouraging elderly people to carry out physical activities according to their capabilities and international recommendations.